ANALYSIS OF THE RIGID PAVEMENT ROAD DAMAGES IN THE SEGMENTS OF PEMALANG - TEGAL: A RESEARCH REVIEWED FROM THE ISSUES OF IMPLEMENTATION AND HANDLING - Sabilirrahman Sabilirrahman; Rachmat Mudiyono (Pondasi, 2019)
Road as a transportation system has an important role in Indonesia compared to other modes of transportation such as air and sea transportation. As road is found to be important, this condition must be maintained to keep it in a good condition. In fact, road damage still occurs that it can bother the road users and disrupt the pace of the economic activities of the community. Therefore, a research is needed to get to know factors that cause damages to the road segments of Pemalang - Tegal. This research belongs to descriptive research conducted by previously testing the validity and reliability of the research approach. It is done by looking for factors that cause damages to rigid pavement roads in terms of implementation, and factors causing the type of dominant damage and how to handle it.This resarch was conducted to 70 respondents using a questionnaires previously tested for validity and reliability. Data were obtained from the questionnaires filled by the respondents and then statistically processed through SPSS and AHP method. The results show that one of the causes of rigid pavement road damage viewed from implementation was the poor material processing system. The most dominant types of damages were abrasion, release of granules and wear. by overlaying in a damaged location.Keywords: Causes, Types of damage, How to handle the road              Road as a transportation system has an important role in Indonesia compared to other modes of transportation such as air and sea transportation. As road is found to be important, this condition must be maintained to keep it in a good condition. In fact, road damage still occurs that it can bother the road users and disrupt the pace of the economic activities of the community. Therefore, a research is needed to get to know factors that cause damages to the road segments of Pemalang - Tegal. This research belongs to descriptive research conducted by previously testing the validity and reliability of the research approach. It is done by looking for factors that cause damages to rigid pavement roads in terms of implementation, and factors causing the type of dominant damage and how to handle it.This resarch was conducted to 70 respondents using a questionnaires previously tested for validity and reliability. Data were obtained from the questionnaires filled by the respondents and then statistically processed through SPSS and AHP method. The results show that one of the causes of rigid pavement road damage viewed from implementation was the poor material processing system. The most dominant types of damages were abrasion, release of granules and wear. by overlaying in a damaged location.Keywords: Causes, Types of damage, How to handle the road